Study Of Dielectric Behavior Of Polymers Using A Complex Electric Modulus - Horák, Luděk (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2021)
The complex electric modulus is mathematically defined as the inverse value of thecomplex permittivity. It is particularly useful in evaluating the dielectric properties of polymericinsulating materials, especially at low frequencies and at high temperatures. Presented thesis isfocused on mathematical interpretation, practical example and evaluation of electrical module.In our case, the measurements are performed on a composite material based on epoxy resin.
Keywords: Complex electric modulus; complex permittivity; dielectric relaxation; compositematerials; electrical insulation materials; epoxy resin